NUTRITIONAL STATUS AND ANEMIA IN PREGNANT WOMEN - Novita, Syarini; Wati, Dewi Fajar (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Anemia affects a significant number of pregnant women in Indonesia, with a prevalence of approximately 48.9%. In Lampung, the incidence remains high, posing serious risks to both mothers and their unborn children due to low hemoglobin levels. This study aimed to determine the effect of nutritional status on the incidence of anemia among pregnant women at the Tanjung Agung Health Center. Using an analytical survey with a cross-sectional approach, the study included 67 first-trimester pregnant women selected through total sampling. Data were obtained from secondary sources, specifically upper arm circumference (LILA) measurements and anemia status recorded on maternal health cards. Findings revealed that 80% of pregnant women with poor nutritional status experienced anemia. Statistical analysis showed a significant relationship between nutritional status and anemia, with a p-value of 0.001 (≤ α 0.05) and an odds ratio (OR) of 8.53. This indicates that pregnant women with poor nutritional status are over eight times more likely to develop anemia. In conclusion, poor nutritional status significantly increases the risk of anemia during pregnancy. The study recommends that families actively support pregnant women by promoting a varied and iron-rich diet and ensuring regular hemoglobin checks during antenatal visits to help prevent complications.